Isodon maoershanensis (Lamiaceae), a new species from Guangxi, South China - Li, Jian-Ling; Tang, Zhong-Xiang; He, Qiu-Lan; Wang, Shao-Neng; Liang, Sheng-Hua; Jiang, Ri-Hong (Phytotaxa, 2024)
Isodon maoershanensis, a new species of Lamiaceae, is described here. The new species is morphologically closest to I. henryi and I. magathyrsus, because of some similar characteristics: leaf blade is hard papery and hairy on both sides, terminal panicle is composed of cymes, style and ovary are hidden in the lower lip of the boat-shaped corolla, filaments below the middle are pubescent, but the new species clearly differs from the latter two, by following characters: the leaf is densely covered with short stiff hairs and scattered glandular points above, with dense red glandular points and sparse stiff hairs along veins below, and the peduncle, pedicel, calyx and corolla are also covered with short stiff hairs and glandular points, at the same time the calyx and corolla are also covered with white long hairs with nodes, calyx lobes split to 1/2 or less.